THE INFLUENCES OF ENTREPRENEURS ISLAMIC PRACTICES ON HALAL SUPPLY CHAIN INTEGRITY: A STUDY IN HERBAL BASED FOOD INDUSTRY - Rajendran, Salini Devi; Kamarulzaman, Nitty Hirawaty (International Journal of Supply Chain Management, 2019)
The use of herbs has grown up in recent years and it is a booming industry in many countries including Malaysia. Locally, thousands of small medium sized companies are dealing with herbal based food products. These companies can produce any food products from botanical plants for multipurpose. However, many of these products sold in the market now may not be manufactured correctly or may have side effects. There is lacking proper scientific data and regulations claimed on those products. The reality proofed that consumers are highly committed to consume high quality products, hygienic, safe and halal which meet the regulatory requirements. Consumers are now well aware of the genuine concept of halalan toyyibban. In the teachings of Islam, halal practices are mandatory for all Muslims. Though the most of Muslims are aware of the Islamic concept and practices, but how their skill and education might influence halal integrity not widely explained. Observing all these matters, this study trying to investigate human capital such as skill, knowledge and experience of small firms entrepreneurs influence on halal integrity of the supply chain focusing on herbs and herbal based food products. The human capital theory is used as underpinning theory to serve as starting-points to develop the conceptual model. From the extensive literature review, entrepreneurs Islamic experience, motivation, training and education were identified to construct the model. Within a halal certified companies, the entrepreneurs motivation, knowledge and skills together with previous business experiences are recognised as important tool in management of business processes in ensuring the halal integrity of the supply chain operations. Thus, it will be useful to study on the impact of entrepreneurs Islamic practices on strengthening halal integrity which can be advantage for an organization. This conceptual model provides an insightful foundation for the analysis of factors influencing halal supply chain integrity. The model proposes that human capital from Islamic perspectives should be considered to support other comprehensive supply chain theoretical frameworks to reflect actual conditions of the industry. Keywords-Entrepreneurs, Islamic practices, halal integrity, halal supply chain